2013
DOI: 10.1093/toxsci/kft105
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside Reverse Transcriptase Inhibitors Induce a Mitophagy-Associated Endothelial Cytotoxicity That Is Reversed by Coenzyme Q10 Cotreatment

Abstract: Cardiovascular complications have been documented in HIV-1 infected populations, and antiretroviral therapy may play a role. Nucleoside reverse transcriptase inhibitors (NRTIs) are antiretrovirals known to induce mitochondrial damage in endothelial cells, culminating in endothelial dysfunction, an initiating event in atherogenesis. Though the mechanism for NRTI-induced endothelial toxicity is not yet clear, our prior work suggested that a mitochondrial oxidative stress may be involved. To further delineate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 53 publications
(69 reference statements)
1
20
0
Order By: Relevance
“…However, while renal and other tissue toxicities are believed to be mediated by mitochondrial oxidative stress (Abraham et al, 2013; Duong Van Huyen et al, 2003; Jiang et al, 2009; Kohler et al, 2009), our studies indicate that targeted antioxidants may also be useful in preventing other NRTI side effects. Our in vitro studies support the concept of adding coenzyme Q10 to current therapies (Xue et al, 2013). Unfortunately, variable results in effects of CoQ10 treatments for mitochondrial diseases have been reported, presumably due to low bioavailability in plasma and tissues after administration (Molyneux et al, 2008; Wyman et al, 2010).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, while renal and other tissue toxicities are believed to be mediated by mitochondrial oxidative stress (Abraham et al, 2013; Duong Van Huyen et al, 2003; Jiang et al, 2009; Kohler et al, 2009), our studies indicate that targeted antioxidants may also be useful in preventing other NRTI side effects. Our in vitro studies support the concept of adding coenzyme Q10 to current therapies (Xue et al, 2013). Unfortunately, variable results in effects of CoQ10 treatments for mitochondrial diseases have been reported, presumably due to low bioavailability in plasma and tissues after administration (Molyneux et al, 2008; Wyman et al, 2010).…”
Section: Discussionsupporting
confidence: 77%
“…In pathological conditions, however, ET-1 production may be increased, not only by endothelial cells, but also in other types of cells, including smooth muscle cells and macrophages (Bohm and Pernow, 2007). Prior work in our laboratory demonstrated that treatment of endothelial cells with AZT, 3TC, or tenofovir induces increases in ET-1 in vitro and that co-treatment with the antioxidant coenzyme Q10 prevents this increase (Xue et al, 2013). In the current study, WT and transgenic mice treated with AZT and 3TC paralleled the in vitro results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only cells from passages 3–8 were used for experiments. The 10 μM doses of drugs were carefully selected according to the International US AIDS Panel, and the average plasma drug concentrations were as previously reported (Chittick et al, ; Jiang et al, ; Xue et al, ). For all in vitro experiments, the cells were treated with drugs for 48 h prior to testing.…”
Section: Methodsmentioning
confidence: 99%
“…One study conducted before effective ART showed no statistically significant difference in CoQ10 levels between HIV-infected patients and uninfected controls 28 . More recently, there is evidence that CoQ10 supplementation may ameliorate the neurotoxicity and endothelial dysfunction associated with the use of mitochondrial toxic ART 3132 . No study has examined CoQ10 changes in response to statin therapy in chronic HIV infection.…”
Section: Introductionmentioning
confidence: 99%